Funkcjonowanie Londyńskiej Giełdy Metali, ze szczególnym uwzględnieniem kontraktów futures oraz opcyjnych wystawionych na miedź rafinowaną - Szeląg, Tomasz (Functioning of the London Metal Exchange, Taking into Consideration Particularly Future and Option Contracts in Copper, 2005)
In the article the London Metal Exchange is described - the world's premier non-ferrous metals market, with highly liquid contracts. The author presents short history of the exchange, its organization, structure and way of functioning. The paper focuses particularly on futures and option CONTRACT. which are used in copper price risk management process. The primary roles of the LME are to provide a market where participants, primarily from non-ferrous base metals related Industries, have the opportunity to hedge against risks arising from base metals price fluctuations, provide reference prices for the worldwide pricing of activities relating to non-ferrous base metals, provide for appropriately located storage facilities to enable market participants to make or take physical delivery of approved brands of non-ferrous base metals. There are three types of copper contracts on the London Metal Exchange, namely futures contracts, options and TAPO contracts. Producers of copper have a possibility to use all of them to manage commodity price risk.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (11); 2005; nr 1077, s. 74-88